Attractiveness Of Visual Communication Elements In Print Advertisement : A Comparative Study In Malaysian Telecommunication Industry - Fikry @ Aziz, Amily (2003)
This study attempts to investigate the attractiveness of 6 Malaysian telecommunication products towards gender and races of tertiary students and identify the elements of visual communication advertising that can attract tertiary students.